The Influence of Hospital Facilities and Services on Patient Satisfaction with Hospital Image as an Intervening Variable at Haji Abdul Manan Simatupang General Hospital - Hamidah Sari Siregar; Yusniar Lubis; Sofiyan Sofiyan (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
The number of complaints from patients who are being treated at the hospital has become evidence that the management of the service system has not paid enough attention to it. So it is necessary to examine in depth the causes of these problems. That is what underlies the researcher wants to find out whether hospital facilities and services have an effect on patient satisfaction with hospital image as an intervening variable at the Haji Abdul Manan Regional General Hospital. This type of research uses causal research which aims to test hypotheses on a causal relationship between one variable and another. The study sample consisted of 315 patients. The results of the study show that hospital facilities have a significant influence on patient satisfaction. Because with the appropriate facilities, patients will feel comfortable visiting the hospital. Likewise, hospital services also have a very large influence on the level of patient satisfaction. With good and comfortable service. Then the patient will get calm and will speed up the healing process for the patient. So it was concluded that quality and service greatly influence patient satisfaction at Umun Regional Haji Abdul Manan Simatupang Hospital.